School Literacy Movement in Improving Student's Critical Thinking Skills in PAI Subjects at Junior High Schools - Cevie Putri, Annisa Ningtias; Rambe, Anggi Afrina; Dwietama, Regita Ayu (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2024)
At this time, literacy is critical to instil in students. Considering the last few years, literacy culture has begun to decline. Even after implementing a proper system, it slowly started to improve. Through cultivating a culture of literacy, the aim is to improve the critical thinking skills of every student through the School Literacy Movement in Islamic Religious Education lessons. This research uses the service method, with literature study as the approach used to collect data regarding related problems. It was concluded that learning Islamic Religious Education can improve critical thinking skills through the School Literacy Movement in Junior High Schools.